An alternative definition for the k-Riemann-Liouville fractional derivative - Dorrego, Gustavo (2015)
The aim of this paper is to introduce an alternative definition for the k-Riemann-Liouville fractional derivative given in [6] and whose advantage is that it is the left inverse of the corresponding of k-RiemannLiouville fractional integral operator introduced by [5]. Its basic properties are discussed, their Laplace transform, the derivative of the potential function and the derivative of the Mittag-Leffler k-function introduced in [2] is calculated.